Mustafa Sabri's Criticism of Political Secularism - Muhamad Fajar Pramono; Deden Ruhiat Mubarok (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses Mustafa Sabri's critical perspective on political secularism, focusing on the dangers, nature, and consequences of the separation of religion and state. Mustafa Sabri, a prominent Muslim in the first half of the 20th century, sharply criticized the ideology of secularism, and revealed that the ideology is not only an ideological deviation, but also an evil plan to abandon religion. Mustafa Sabri identified the essence of secularism as the separation between Islamic governance and religious principles, described religion as the loss of authority over governance, and pointed out negative consequences such as the loss of morality and degradation of values. This paper provides a detailed overview of Mustafa Sabri's views on political secularism, discusses his critique of the dangers of secularism, explains in detail the nature of the separation of religion and state, and describes the possible negative impacts for Islam. This paper is useful for those who want to understand the Islamic perspective on political secularism.